Demonstration of System Technologies Enabling Millimeter Wave Power Beaming Using Thermomechanical Power Conversion - Anthony E. Baros; Brad W. Hoff; Kenneth M. Armijo; Charles E. Andraka; Paul Pelletier; Ender Savrun; Ian M. Rittersdorf; Joseph W. Schumer; Zane W. Cohick; Samuel C. Schaub (IEEE Journal of Microwaves)
Key technologies and system components for a power beaming concept, based on a high-power mm-wave transmitter and thermomechanical conversion of the beamed energy to electrical power at the receiving station, are described. Outdoor testing was performed at a test range at Kirtland Air Force Base, New Mexico. The transmitting and receiving stations were located 350 m apart. The 95 GHz gyrotron oscillator within the transmitter system was operated at 90 kW, which after optics and antenna inefficiencies, resulted in approximately 68 kW of power in the main lobe of the Gaussian mm-wave beam at the location of the receiving station. A portion of the beam (37 kW) was intercepted by the aperture of the receiving station's beam collector and directed onto the surface of a heat exchanger which used an array of embedded ceramic susceptors to convert the incident mm-wave beam to heat which is transferred to the working fluid of a SOLO-161 Stirling engine generator unit. Of the 31 kW of mm-wave beam power concentrated at the surface of the heat exchanger by the beam collector, it is estimated that approximately 58% is converted to heat. Limitations on the operating duration of the transmitter at the time of the experiments prevented the Stirling engine generator from achieving full start-up and electrical power generation, necessitating future experiments to demonstrate full “end-to-end” electrical power delivery.